Institutional determinants of environmental performance - Reichel, Richard (Energy Economics Letters, 2023)
This note examines the impact of three institutional factors on environmental performance and carbon intensity of gross domestic product (GDP) for a cross-section sample of 154 countries. The institutional factors are democratization, market orientation of the economy, and prevalence of corruption. Per capita income is generally used as a control variable. As the distribution of some of the variables is highly skewed, we apply several robust regression methods, in comparison to ordinary least squares (OLS). Results differ depending on the estimation method, but generally per capita income is negatively related to carbon intensity but positively correlated with environmental performance. The higher the degree of democratization, the better the state of the environment and the lower the carbon intensity. Market orientation of the economy is ambiguous at first sight, but if an interaction variable with the democracy index is applied, the effect is quite large and highly significant. In this case, the impact of the corruption variable fades. Sensitivity analyses reveal, that introducing a democratic market economy is the most promising strategy to promote environmental performance as well as to cut the carbon emission intensity.